2008
DOI: 10.1176/ps.2008.59.12.1419
|View full text |Cite
|
Sign up to set email alerts
|

Pay for Performance in Behavioral Health

Abstract: The authors reaffirm the finding identified by the Leapfrog Group's "Rewarding Results" initiative--that is, pay for performance is not a magic bullet that alone will improve quality and control costs. Although pay-for-performance programs hold promise for advancing the overall performance of the U.S. health care system, more intensive efforts aimed at strengthening the quality infrastructure in behavioral health will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Within the behavioral health treatment field, however, P4P has been less common, with only 13 P4P programs having been identified that targeted either behavioral health specialists or substance abuse treatment providers (Bremer, Scholle, Keyser, Houtsinger, & Pincus, 2008). In general, behavioral health P4P programs have focused on increasing rates of client engagement and retention in treatment and have provided incentives at the level of the treatment program.…”
Section: Introductionmentioning
confidence: 99%
“…Within the behavioral health treatment field, however, P4P has been less common, with only 13 P4P programs having been identified that targeted either behavioral health specialists or substance abuse treatment providers (Bremer, Scholle, Keyser, Houtsinger, & Pincus, 2008). In general, behavioral health P4P programs have focused on increasing rates of client engagement and retention in treatment and have provided incentives at the level of the treatment program.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also contributed additional information about the use of both financial (bonus payment) and non-financial incentives (education and feedback) to individual clinicians to encourage improvement in care for depression. Previous work has primarily centered on financial incentives (Bremer et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…These programs used a variety of approaches to change the economic and organizational environment to improve care for depression, including developing new payment and billing mechanisms as well as restructuring delivery systems to better target care (Feldman, Ong, Lee, & Perez-Stable, 2006; Grazier & Klinkman, 2006; Labby, Spofford, Robison, & Ralston, 2006; Thomas, Waxmonsky, McGinnis, & Barry, 2006). A recent study identified 24 programs that use pay-for-performance approaches in behavioral health (Bremer, Scholle, Keyser, Houtsinger, & Pincus, 2008). Of the 13 programs that targeted behavioral health specialists, nine were sponsored by behavioral health plans and only two focused specifically on depression as a target condition.…”
Section: Introductionmentioning
confidence: 99%
“…They are only beginning in SU and psychiatric treatment, again partly because of the difficulty of defining appropriate quality indices 72. In addition, the immaturity of information technology systems in both fields has made it more difficult to collect and report the data needed to implement P4P mechanisms.…”
Section: Opportunities For Increasing Accessmentioning
confidence: 99%